Study on Livelihood through Adaptation and Diversification in Flood Prone Areas in West Bengal - Sarkar, Debashis; Hazra, Sumantra (International Journal of Applied Sciences and Biotechnology, 2014)
The study points out the need for third party intervention in promoting the livelihood patterns which are less exposed to the damaging effects of flood. Self-employment in small business or trading is a good option for households to supplement their streams of income. But such business even though required small capital, required at least some degree of training and skills development. Therefore, the financing and consultancies agencies can intervene. Promotion of ancestral occupation based on traditional skills and local level resources may be considered. Once again intervention of government and non-government organizations is highly required. Similarly, non-farm wage employment can also be promoted by introduction of “year round” public projects and employment guarantee schemes. Promotion of activity-wise micro financing, self-help groups may be involved. However, none of the areas as identified can be taken sufficient to substitute the flood risk prone livelihoods as most of them are directly or indirectly dependent on agriculture in the context of a farming community. DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11217Int J Appl Sci Biotechnol, Vol. 2(4): 446-450